Decision Support System Pemilihan Karyawan Berprestasi Dengan Pendekatan Analisa Gap Profile matching Di Kantor Perwakilan Bank Indonesia Provinsi Aceh - Munawir Munawir; Ardiansyah Ardiansyah (KITA Institute, 2017)
One method of decision support system is the method of profile matching, this study builds a decision support system in the selection of outstanding employees at the Bank Indonesia Regional Office of Aceh Province which is expected to assist decision makers in deciding the best alternatives in the selection of outstanding employees. By using profile matching that can process and compare the actual data value of a profile to be assessed with the expected profile value, so it can know the difference of competence (also called gap), the smaller the resulting gap the greater the value of value which means have the opportunity greater to be recommended as an outstanding employee. Decision Support System (DSS) can take into account all the criteria that support decision-making to help speed up and simplify the decision-making process. The results of this study will generate a ranking ranking of employees and this application can assist decision makers (decission maker) in choosing an alternative employee who excel.